Casting The Shadows of Doubts: : The Perspectives of Teachers in the Employment Process - Princess Marynee V. Morga; Reena Mae Niῇa S. Lustan; Lyndon Quines; Geraldine D. Rodriguez (International Journal of Educational Administration, Management, and Leadership, 2021)
This study aims to describe the perspectives of teacher applicants in the employment process. Qualitative phenomenological approach was employed to three teacher applicants who belonged to one division and experience the employment process ranged from school year 2016 to 2020. To gather data, in depth interview was conducted. The results of the interview were transcribed, translated and coded to produce themes. As regards the experiences of teacher applicants, two themes were formulated: first, patiently waiting for the future and second is steadiness and sanguinity. Looking on how they cope with the employment process, the following themes were created: support system, welcoming the possibilities and realization overload. As to their insights, the following themes were generated: time tested values and pursuing dreams in the test of time. The hiring process is a battleground. Teacher candidates put forth a lot of effort in their preparation. The eventual conclusion could have a wide range of consequences for each applicant. Teacher candidates use coping methods such as cognitive, emotional, and behavioral comforting and adaption strategies to deal with stressful circumstances, particularly during the hiring process, and to decrease distress. Every teacher applicant has unique experiences, but the learning and character development gained during the process brought them all together; these are the hope for a secure future and a desire to contribute meaningfully to the nation's growth by educating the nation's future. It is not necessarily the pay and benefits that convince people that this is a vocation, but rather the heart.